A Protocol for Cancer-Related Mutation Detection on Exosomal DNA in Clinical Application - Wang, Zhe-Ying; Wang, Rui-Xian; Ding, Xiao-Qing; Zhang, Xuan; Pan, Xiao-Rong; Tong, Jian-Hua (Frontiers in Oncology, 2020)
Background: Recently, some genomic mutations in exosomal DNA have been found to be related to disease progress and clinical outcomes of patients in several cancers. Unfortunately, the methods for exosome isolation and exosomal DNA analysis are still lack of relevant research to ensure their optimal performance and the comparability. Here we aim to establish a protocol for cancer-related mutation detection on exosomal DNA in clinical application. Methods: Taking KRAS mutation in pancreatic cancer as an example, we tested whether the types of blood samples, the potential factors in the courses of exosome isolation and exosomal DNA preparation, as well as the detail in mutation detection by droplet digital PCR (ddPCR) could influence the exosomal DNA analysis. Results: We found that the concentration of exosomal DNA from serum was higher than that from plasma, whereas the mutant allele fraction (MAF) of KRAS in serum-derived exosomal DNA was obviously lower. The membrane-based method for exosome isolation showed no evident difference in both exosomal DNA yield and KRAS MAF from the classical ultracentrifugation method. DNase I pretreatment on exosomes could remove the wild-type DNA outside of exosomes and increase the KRAS MAF. PBS might interfere with the effect of DNase I and should not be recommended as resuspension buffer for exosomes if the subsequent experiments would be done with exosomal DNA. Besides, the denaturation of exosomal DNA before droplet generation during ddPCR could effectively improve the total KRAS copy number and mutation-positive droplet number. Conclusion: This study provides some methodological evidences for the selection of the optimal experimental conditions in exosomal DNA analysis. We also suggest a protocol for mutation detection on exosomal DNA, which might be suitable for the clinical testing and could be helpful to the comparison of results from different laboratories.